"In the beginning..." - Rice, John R. 1895-1980 (Murfreesboro, TN Sword of the Lord, 1975)
Includes bibliographical references.
Keywords: Bible. O.T. Genesis -- commentaries; Creation -- evidences; Deluge -- evidences